The Prevalence of Overfat Adults and Children in the US - Maffetone, Philip B.; Laursen, Paul B. (Frontiers in Public Health, 2017)
The overfat condition is defined as excess body fat sufficient to impair health. The problem exists in most overweight and obese individuals and can also occur in those who are normal-weight and non-obese, often due to excess abdominal fat. Despite previous indications that the prevalence overweight and obesity is leveling, these conditions are currently at their highest levels in US history. Our review estimated the number of overfat Americans at 91% for adults and 69% for children. The primary purpose of this review was to build upon previous estimations of overfat prevalence in developed countries by using new data from the Centers for Disease Control and Prevention to estimate the overfat prevalence in American adults (≥20 years) and children (2–19 years), and to expand the definition of overfat as excess body fat associated with at least one additional risk factor of impaired cardiometabolic or physical health. The secondary goals are to highlight the role of dietary sugar as a primary cause of the overfat pandemic and mention new data showing the increased prevalence of exercise that parallels the rising prevalence of overfat to further emphasize the secondary role exercise may play in fat loss. Current public health guidelines to address the overfat pandemic may require more emphasis on reducing the consumption of refined carbohydrates, including added sugars.